Geomorphic Study of the Deccan Trap: A Case of Relief and Slope Analysis - Singh, R.Y (National Geographical Journal of India, 2022)
The area under study (Manpur and Environs, M.P. ( India) lies between latitudes 22° 20' N and 22° 30' N and longitudes 75° 35' E and 75° 44’ E, covering an area of slightly over 361 km? (Fig. 1). It shares mostly the south-western portion of Mhow Tahsil and small portion of northern part of Barwaha Tahsil in Indore and West-Nimar districts respectively in Madhya Pradesh State of India. The preference given to this area was largely due to variations in landscape features representing hills, plateau, gorge, falls, peaks, scarps, meanders, drainage divides and erosion surfaces. The area has two systems of drainage. Physiographically it contains eleven geomorphic divisions with several accordant summit levels. Relative relief has no bearing with the absolute relief. Absolute relief has little relation with dissection index. Its maximum frequencies lie in the category of low dissection index which encompasses about 84% of the area. Plateau has low, divides and slopes moderate while gorges and scarps have high dissection index. Wentworth’s method has been used for quantitative generalizations. Gradient ranges from less than 1/ 80 to less than 1/1.5. The tract has been classified into four generalised categories of slope . Beside, qualitative slope groups have also been suggested. A careful observation and investigation in the field leads us to trace four erosional surfaces which, along with other features, present evidence ofa polycyclic landscape.